The ROLE OF MARKETING PUBLIC RELATIONS (MPR) IN MODERATING THE PRICE STRATEGY ON CUSTOMER AWARENESS OF GERAKAN PANGAN MURAH (GPM) ACTIVITIES IN JAMBI CITY - Elsa Miranda.R; Yacob, Syahmardi; Yuniarti, Yenny (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study aims to analyze the role of marketing public relations (MPR) in moderating price strategies for customer awareness in the activities of the Gerakan Pangan Murah (GPM) in Jambi City. The research method used is a quantitative approach with analysis techniques using SmartPLS version 4.0. The sample in this study consisted of 96 respondents who were selected through purposive sampling techniques. Data collection was carried out through observation, questionnaires and literature studies. The results of the study show that pricing strategies have a positive and significant influence on customer awareness. In addition, marketing public relations also has a positive and significant effect on customer awareness. Testing the effect of moderation shows that marketing public relations plays a role in moderating the relationship between marketing public relations and pricing strategies, but marketing public relations as moderation plays a role in weakening the relationship between price strategies and customer awareness. The implication of this study emphasizes that companies need to pay attention to the policies of marketing public relations to increase customer audience effectively. Because the company does not only rely on price strategies in building customer awareness. Therefore, it is necessary to balance the pricing strategy with marketing public relations so that marketing can be achieved optimally.